Pengembangan Dan Penjabaran Indikator Wirausaha Berbasis Ilmu Pendidikan - Supriyanto, Dadang; Hidayatulloh, Dadan; Nurjaman, Ujang (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Entrepreneurship has become a key pillar in economic and social development worldwide. As a process involving opportunity identification, innovation, and new venture creation, it drives economic growth, job creation, and societal welfare. In this context, entrepreneurial education plays a crucial role in fostering the necessary skills and mindset. Through well-designed programs, individuals gain the knowledge and attitude to succeed as entrepreneurs. However, a significant challenge remains: measuring the effectiveness of entrepreneurial education due to the lack of clear indicators. This study focuses on developing measurable indicators to assess entrepreneurship education outcomes, ensuring the programs' success in nurturing entrepreneurial skills and values. Key indicators include religiosity, noble character, creativity, independence, and environmental awareness, emphasizing the importance of integrating national culture into entrepreneurship development.